Pengaruh Intellectual capital, Good Coporate Governance dan Ukuran Perusahaan terhadap Kinerja Keuangan - Rizki Nur Anisa; Mirna Dyah Pratitorini (CV. Ulil Albab Corp, 2024)
This study aims to examine the effects of intellectual capital, good corporate governance (GCG), and company size on the financial performance of banking companies listed on the Indonesia Stock Exchange (BEI). The results indicate that intellectual capital has a positive and significant impact on financial performance, suggesting that increasing a company's intellectual assets can improve financial outcomes. Good corporate governance also has a positive and significant impact on financial performance, showing that implementing sound governance practices enhances investor confidence and operational efficiency. However, company size was found to have a negative and insignificant effect on financial performance, indicating that size growth does not necessarily lead to increased efficiency or profitability. This study highlights the importance of managing intellectual capital and implementing good corporate governance to improve the financial performance of banking companies.